SELECTION OF MATERIALS USING MULTICRITERIA DECISION MAKING. A CASE STUDY ON CELLULAR MATERIALS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
In recent years, many companies have been striving to transition towards a sustainable, circular economy, focusing on the efficient use of materials and environmental protection. This has become a strategic necessity. One promising approach is the replacement of traditional sheet metals with cellular metal materials, such as perforated metal sheets, expanded metal, welded picket fences, and woven wire mesh. This substitution offers both environmental and economic benefits, while also supporting eco-technological innovations in regional industries. To evaluate the applicability of specific cellular metal materials, several factors must be considered, including the potential for weight reduction, noise reduction, and other environmental impacts. This article presents a multi-criteria decision-making methodology applied to the category of cellular materials, using the example of a perimeter fence in an urban environment. It provides a detailed overview of the types of materials, production methods, and the most significant factors of advantage. The main objective is to highlight the benefits of cellular materials. The primary objective is to highlight the benefits of cellular materials. A group expert assessment method was employed in this study. Findings indicate that perforated metal materials are most popular in properties to Cellular Materials (CMs). However, experts assess that CMs offer unique advantages in construction, design, and environmental sustainability compared to braided or expanded alternatives.